MANAGEMENT OF SHEATH BLIGHT OF RICE USING DIFFERENT SOLVENT-BASED PLANT EXTRACTS (Journal of Plant Disease Sciences, 2023)
Rice ( L.) belong to the Gramineae family is themost extensivelygrown food crop in the world and about 90 per cent of rice grown in the world isproduced and consumed in Asia. Sheath blight is one of the most destructive ricediseases, foundthroughout theworld’s rice-growing regions. Inpresent investigationdifferent solvent based plant extracts were evaluated against sheath blight of riceaswell as . Results indicated that Hexaconazole 5%SC (100%),Methanolbased neem extract(100%), Methanol based plant extract mixture (100%), Ethanolbased plant extract mixture (100%) and Ethanol based neem extract (100%)completely inhibited the mycelia growth of at 10 per centconcentration Cow urine-based plant extracts were found significantly effective insuppressing the sheath blight severity and increasing the yield over control plot.Lowest per cent disease index (PDI) was observed in Hexaconazole 5% SC @0.1%(PDI-8.08%)whichwas found to bemost effective and at par with Hexaconazole 5%SC @0.05% (PDI-8.88%) followed by Pure Cow urine (5%) Hexaconazole 5% SC@0.05% (PDI-9.35%) and Cow urine-based plant extracts mixture (5%) +Hexaconazole5%SC@0.05%(PDI -9.60%) over control.PureCowurine@10%, (PDI–27.81%) and Cow urine-based plant extracts mixture@10 % (PDI –29.61%) werealso found significantly highly effective controlling sheath blight disease andstatistically at parwith each other. Combination ofhalfdoses of Pure Cowurine (5%)+ Hexaconazole 5% SC @0.05% (PDI-9.35%) was found significantly effective as compare tocontrol.
Keywords: Rice; Sheath blight; Plant extracts,; , Cow urine